Phytochemical Investigation, Antimicrobial, Antioxidant and Anticancer Activities of Acer cappadocicum Gled - Kausar, Farzana (Life (Basel), 2021)
The appearance of novel microbial resistance, diverse cancer ailment and several other morbidities such as appetite loss, hair loss, anemia, cell damage, etc., are among most critical situation that keeps the phytochemical quest on. Thus, this study characterized the antimicrobial, antioxidant, and anticancer potentials of a rarely accessed Acer cappadocicum gled (AC) population thriving in a remote Palas Valley in northern Pakistan. Leaf extracts of the plant were prepared in organic solvents with different polarities through maceration. Extracts were subjected to antimicrobial, antioxidant, and anticancer activities using agar well, DPPH and cell viability assays. A. cappadocicum methanolic extract (ACM) significantly inhibited bacterial growth, followed by n-butanolic extract (ACB) with the second-highest bacterial inhibition. Similar activity was observed against mycelial growth inhibition in plant-fungal pathogen by ACM and ACB. However, human pathogenic fungi did not affect much by extracts. In antioxidant assessment, the chloroform extract (ACC) showed strong scavenging activity and in cytotoxic evaluation, extracts restricted growth proliferation in cancer cells. The inhibitory evidence of extracts, potent scavenging ability, and low cell viability of human-derived cell lines supports the antimicrobial, antioxidant and anticancerous potential of A. cappadocicum. It advances our quest for natural product research.